Donne italiane e donne argentine tra tradizionalismo ed emancipazione - Zenia Simonella; Stefania Chimenti (Cambio)
Contributing to the debate on gender equality, the article analyses gender differences by age group. We build an index of traditionalism – based on dimensions namely «familism», «religiosity», and «localism», by analyzing 3.923 Italian cases and 2.578 Argentinian cases collected in the context of a piece of international independent research about values, called «Identity and Nature», coordinated by Alberto Marradi. Argentina appears to have a higher index of traditionalism and much more pronounced gender differences even among young people. In Italy, there is a levelling off between women and men in the younger age groups and a greater distance with the older ones, showing that cultural change is proceeding faster, thanks to the increase in the level of women’s education. Argentina is also experiencing the same phenomenon in education, however the process is slower, and so is women’s emancipation. Limits of the work and future research directions are discussed in the conclusion.